Peningkatan Aktivitas dan Hasil Belajar Akidah Akhlak melalui Metode Market Place Activity pada Siswa Kelas XI-MIPA 4 MAN 3 Sleman Yogyakarta - St Darojah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
This research aims to improve the activity and learning outcomes of Akidah Akhlak through the implementation of Market Place Activity method of Flow Kalam in class XI-MIPA 4 MAN 3 Sleman. The design of this research is class action research (PTK) which takes place in two cycles. The subject of this study was the students of the XI-MIPA 4 MAN 3 Sleman class as many as 31 people. Data collection is done by observation method to observe the level of learning activity and test method to find out the result of learning outcomes of Kalam flow material in the form of a double choice of 20 questions, given every end of the cycle. The results of study activities learned from a pre-active student cycle of 23% then on the I cycle increased to 51% and in cycle II increased to 87%. The results of the student learning pre-cycle value of 68 to reach 32%. Then at cycle 1 the average value increased to 78 with a close to 68%, on the cycle II the average value increased to 86 and the compensation reached 90%. Based on the research results from Cycle 1 and cycle 2 indicates that the implementation of the Market Place Activity (MPA) method of activity and student learning results are improved.